Answer:
x = -5
![(4)/(7)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/p08jqre9fqz082ojc33asowtorqn6abs3v.png)
Explanation:
All we need to do is to find the value of x
4×+3=-9-3(×+9)
First we will open-up the bracket, to do that -3 will be use to multiply all the values in the bracket
4x + 3 = -9 -3x - 27
Then we will now collect like term, all x variables will be on the left-hand side and all constant will be on the right-hand side
To do this, we will add 3x to both-side of the equation and then subtract 3 from both-side of the equation
4x +3 +3x = -9 -3x + 3x - 27
7x + 3 = -9-27
7x + 3 - 3 = -9-27-3
7x =-39
Divide both-side of the equation by 7
7x/7 = -39/7
(On the left-hand side of the equation, 7 at the numerator will cancel-out 7 at the denominator leaving us with just x and on the right-hand side of the equation -39 will be divided by 7
x = -5
![(4)/(7)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/p08jqre9fqz082ojc33asowtorqn6abs3v.png)